The best strategy to control pain after thoracic surgery: multimodal strategy against pain - Rizzi, Alessandro; Raveglia, Federico; Scarci, Marco; Cioffi, Ugo; Baisi, Alessandro (Video-Assisted Thoracic Surgery, 2019)
Pain has always been a concerning and main topic in thoracic surgery. Thoracotomy (was) is the traditional access to reach pleural cavity. This allows to have a very great management of all the thoracic organs through a direct and wide costal split. There are different types of thoracotomies that can be done; each gives different exposure of the thorax and for every case surgeons must be able to adopt one of those for specific necessities (1-9). Surgical approach must be chosen not only on operative target but also evaluating the impact on patient recovery and kind of analgesic therapy available and applicable. A lot of modified procedures, both surgical and analgesic, have been studied and introduced (2); the aim was to reduce the impact on chest wall and subsequently the arise of pain, both acute and chronic that are actually the most frequent and dreadful morbidity (3,4).